From criminal principiology to the right to intimacy as a constitutional guarantee - Greco, Rogério; Palitot Braga, Romulo Rhemo (Direito e Desenvolvimento, 2021)
The current text presents an initial reflection on the importance of the Penal Law and its principles, expressed or implicit in a positivistic perspective. They should be understood as informants of all the juridical order with the capacity to ascertain the validity under constitutional class rules, occupying, in this way, a hierarchically superior place. It will also be considered, the bond between Penal Law and the recognition of the principle of the dignity of the human person, especially regarding the right to intimacy. The technique used to the bibliography